The stratigraphy and structure of the Kommadagga subgroup and contiguous rocks - Swart, Roger (Rhodes University, Faculty of Science, Department of Geology, 1982)
The Lake Mentz and Kommadagga Subgroups were deposited in a marine environment and are characterised by a heterogeneous sequence of sediments, which range in grain size from clays to grits. During the first phase of deposition the Kweekvlei Shale and Floriskraal Formations were deposited in a prograding shoreline environment, whereas the succeeding Waaipoort Shale Formation is interpreted as represnting a reworked shoreline . The final phase of deposition of the Cape Supergroup was a regressive one in which the Kommadagga Subgroup was formed. The coarsening upward cycle of this subgroup represents a deltaic deposit. A significant time gap appears to exist before the deposition of the glacial-marine Dwyka Tillite Formation. Structurally, the area was subjected to deformation by buckle folding at about 250 Ma into a series of folds with southward dipping axial planes. Only one phase of deformation is recognised in the study area . A decrease in pore space, mineral overgrowths,formation of silica and calcite cements and development of autigenic minerals such as opal, stilpnomelane, analcite, prehnite, muscovite and various clay minerals are the characteristic diagenetic features of the sediments. The mineralogical evidence suggests that the maximum temperature and pressure of burial was 150 C and 4 to 5 Kbar respectively.
Keywords: Uncatalogued